Optimizing Rural Development: Strategic Implementation of the Village Fund Policy for Sustainable Community Empowerment: Optimalkan Pembangunan Desa: Implementasi Kebijakan Dana Desa untuk Pemberdayaan Masyarakat Berkelanjutan - afifah, Ike Nur; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2023)
This descriptive qualitative study investigates the implementation of village fund policies in Kemiri Village, Sidoarjo District, Sidoarjo Regency, employing observation, interviews, and documentation as data collection methods. Through purposive sampling, the study analyzes the clarity of information on village funds in alignment with the Ministry of Finance's directives, focusing on development and community empowerment. The results demonstrate optimal implementation, showcasing the village government's commitment to inclusive decision-making, ensuring community involvement and support for planned initiatives. This research contributes insights into effective local governance practices, with implications for policymakers and practitioners seeking to enhance the impact of village fund policies on rural development and community empowerment. Highlight : The study employs a descriptive qualitative approach to assess the optimal implementation of village fund policies in Kemiri Village, Sidoarjo Regency. Data collection involves observation, interviews, and documentation, employing purposive sampling to analyze the clarity of information on village funds in alignment with Ministry of Finance directives. Findings reveal a commitment to inclusive decision-making by the village government, ensuring active community involvement and support for planned initiatives, offering valuable insights for policymakers and practitioners in rural development Keywords: Village Fund Policy, Implementation, Community Empowerment, Local Governance, Rural Development.